The Syrian refuge in Jordan and its impacts on the national security - AHMAD A’REF ALKAFARNEH (Journal of Advanced Research in Social Sciences and Humanities, 2020)
Aim: The study’s overarching goal is to examine the threat to Jordanian security posed by the ongoing situation in Syria. To demonstrate the significance of setting up refugee reception centers along the Jordanian and Syrian borders.Method: Qualitative research methods were employed to gather data on asylum seekers. The data originated from various online resources.Findings: According to the data, hundreds of thousands of people have entered Jordan as refugees through its northern borders in the past few years. Moreover, this massive migration took place as people fled the security in Syria in search of safety and medical care for their loved ones who had been injured in the conflict. Because of the large influx of Syrian refugees that entered Jordan at the start of September, the government established the Za’atari refugee camp there. Because of this, on September 7th, 2012, the Cabinet of Jordan decided to open emergency refugee camps in the kingdom and invite Syrians to come and live there.Implications/Novel Contribution: This research is vital because it can be used for security and statistical purposes in dealing with the urgent security-related imbalances due to the influx of Syrian refugees. Additionally, a scientific overview of an urgent national problem can be made available to libraries. By the end of the day, this research will aid in the search for viable solutions to the crisis in Syria.